Estudo clínico-patológico dos tumores bucais de origem perineural e análise imunoistoquímica dos antígenos S-100 e CD57 nos diferentes tipos de lesão - Franco, Talita (2012)
Peripheral nerve sheath tumors (PNST) are neoplastic or reactive diseases of rare occurrence in the oral cavity, whose diagnosis can be challenging. This study aimed to gather epidemiological and molecular information to improve biological characterization of PNST, favoring the differential diagnosis between them. After histological review, clinical and demographic data from TBNP evaluated between 1978 and 2010 by the Oral Pathology Laboratory of Federal University of Uberlândia, were organized, followed by immunohistochemical analysis of molecules S-100 and CD57. We found 29 cases (0.27% of total sample), corresponding to 6 traumatic neuromas (TN), 7 neurofibromas (NF), 7 schwannomas (SW), 5 granular cell tumors (GCT) and 4 palisaded encapsulated neuromas (PEN). There was no significant sex predominance, most patients were young adults, the tongue was the most affected anatomical site, and the tumors were usually asymptomatic. All tumors showed diffusely reactivity for S-100. Diffusely reactivity for CD57 was observed in TN, on rare parenchymal cells of SW and PEN, and none of them in NF. In addition, reactive nerve fibers permeated cases of NF, GCT and PEN, but not in SW cases. In conclusion, this study confirms the rarity of PNST in oral mucosa and clinical similarity between them, also the constant expression of S-100, demonstrating their probable shared origin. Finally, the observed rare or absent expression of CD57 shows that tumor s Schwann cells do not reach complete differentiation, but are found in GCT; moreover, the arrangement of nerve fibers may eventually be useful for diagnostic differentiation between different PNST.